Assessing Financial Condition of local Government in Indonesia: an exploration - Ritonga, Irwan Taufiq; Clark, Colin; Wickremasinghe, Guneratne (Business Perspectives, 2012)
This study develops a concept to assess financial condition of local governments (LG) and implements the concept into local governments in Indonesia. This is an exploratory study because of the limitation of research focusing in local government financial condition. In the context of Indonesia, to the author's knowledge, this study is the first in proposing concept to assess the financial condition of local government. The concept consists of six dimensions, namely short-term solvency, long-term solvency, budgetary solvency, service-level solvency; financial flexibility, and financial independence. Each dimension has its own indicators. There are a total of nineteen indicators examined in this study. The exploration shows that local governments have good financial condition for dimension of short-term solvency, long-term solvency, and financial flexibility; adequate financial condition for budgetary solvency; and weak financial condition for financial independence. For the dimension of service level solvency, there is improving condition in delivering services to the community as indicated by the increasing trend of the ratios of service level solvency. Stakeholders of local government perceive the dimension of long-term solvency and short-term solvency are the two most important dimensions and the dimension of service level solvency is considered as the least important element of the financial condition. These facts indicate that the stakeholders tend to have short-term horizon rather than long term in managing local government finance. The results of assessing financial condition could be used by local governments and their stakeholders to enhance public accountability, to rank local government bonds, and to increase local government competitiveness. Keywords: financial condition, local government, short-term solvency, long-term solvency, budgetary solvency, service-level solvency, financial flexibility, financial independence. JEL Classification: H70, H71.